Perbandingan Aktivitas Ekstrak Etanol Kulit Pisang Kepok Kuning Dengan Ekstrak Etanol Kulit Pisang Kepok Mentah Terhadap Bakteri Salmonella typhi Penyebab Tifus - Andi Nurpati Panaungi; La Sakka (Journal Syifa Sciences and Clinical Research, 2022)
Research has been carried out by testing the antibacterial activity against Salmonella typhi using the diffusion method on NA medium with 3 times replication. Each concentration used was 1.25%, 2.5% and 5.0%. The results obtained show the zone of inhibition around the paper disk with different diameters for each concentration. For raw kapok banana peel with a concentration of 1.25% is 9.82 mm, 2.5% concentration is 10.54 mm and 5.0% concentration is 11.39 mm, while the positive control chloramphenicol is 14.14 mm and the control negative, no inhibition was found and for yellow kapok banana peel with a concentration of 1.25% was 6.67 mm, 2.5% concentration was 7.47 mm, 5.0% concentration was 8.58 and positive control chloramphenicol was 14, 5mm. So it can be concluded that the ethanol extract of raw kepok banana peel (Musa paradisiaca L) has a greater inhibitory power than yellow kapok banana peel (Musa paradisiaca L) against the growth of Salmonella typhi bacteria. It is hoped that further researchers will be able to conduct research on other microbes